Stroke hospitalization trends of the working-aged in Finland - Jussi O. T. Sipilä; Jussi P. Posti; Jori O. Ruuskanen; Päivi Rautava; Ville Kytö (PUBLIC LIBRARY SCIENCE, 2025)
BackgroundThe age-standardized incidence of stroke has decreased globally but, for reasons unknown, conflicting results have been observed regarding trend in incidence of major stroke subtypes in young adults. We studied these trends among people of working age in a population-based setting in Finland, where cardiovascular risk factor profiles have developed favorably.MethodsAll hospitalizations for stroke in 2004-2005 and 2013-2014 for persons 18-64 years of age were identified from a national register. The search included all hospitals that provide acute stroke care on mainland Finland.ResultsHospitalizations for both intracerebral hemorrhage (ICH; -15.2%; p = 0.0008) and subarachnoid hemorrhage (SAH; -26.5%; p<0.0001) decreased overall and for both sexes separately. Concerning IS, hospitalizations decreased only for men (-6.3%; p = 0.0190) but not for women or overall. However, there was an increase in IS hospitalizations in men 35-44 years of age (+37.5%; p = 0.0019). The length of stay (LOS) of IS patients declined in nearly all subgroups (overall -20.8%, p<0.0001) whereas no change in LOS was observed for patients with ICH or SAH. In-hospital mortality decreased in patients with IS (-42.8%; p = 0.0092) but remained unchanged in patients with ICH or SAH.ConclusionsStroke hospitalizations of young people declined in Finland, except for men 35-44 years of age for whom IS hospitalizations increased. Declining LOS and in-hospital mortality of IS patients suggests admission of less severe cases, improved care or both.